A Framework For Transitioning Of Traditional Software Development Method To Distributed Agile Software Development - Singh, Madan; Chauhan, Naresh; Popli, Rashmi (2019 International Conference on Issues and Challenges in Intelligent Computing Techniques (ICICT), 2019)
Plan driven methods or traditional methods of software development developers know all the requirements in advance because they are stable in nature. In the challenging world of software development where customer opinion and demands are changing on day to day basis, these traditional methods cause project failures due to poor customer communication and rigid time frame structures. Agile Software Development (ASD) is software development methodology that emphasizes on adaptability. Due to which it satisfies customer - centered development that supports quick and flexible response to change. Distributed Agile software development (DASD), is a methodology in software development paradigm where development teams are distributed in different countries across the globe. In this paper we have proposed a framework for transitioning of traditional software development method to Distributed Agile Software Development. The proposed framework addresses time - zone based problems in Distributed Environment.